(3MSf GdLeY ajeG bjd aj bUQ GdTeYs - (3GdUHGZ , ejNGFjd Hf fbhdG Hf EHQGgje,J (B1232 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi bO JfRg Yf GdJZjjQ hLYd GSJMGdGJ GdCTjGA YHQI ddUZjQ hGdcHjQ s
(3BNQgG (B:s
(3Je HMeO Gddg hced ai OGQ eWHYI SdWfI aQfSG s
(3Cdag GdeDda HETGQI ef eQSd CejQ eWHYI SdWfI aQfSG hLfQGdgG hQJHg Ydi SJI aUhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B338 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B62s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B479 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B115 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3JGQjN (B2359) s
Keywords: (3GdJGQjNs